Numerical Assesment of a Small-Scale and Very Low Tip Speed Ratio Wind Turbine - Bourhis Martin (EDP Sciences, 2021)
The aim of this paper is to study by CFD the performance and to characterize the velocity fields in the wake of an horizontal axis wind turbine. The design of this wind turbine is far from classical as it has been designed to work at very low angular velocity to promote torque. The 8 blades are not isolated but form a high solidity blade cascade. The numerical simulation compares well to experimental data regarding the power coefficients. The analysis of the wake does show that high tangential velocities, close to the order of magnitude that was used as a design requirement, are generated and form a stable rotating wake. This rotating kinetic energy in the wake may be used to rotate a second rotor in a counter-rotating arrangment.